Study on thermo-kinetic modeling of green route synthesized inorganic loading on PVDF membrane for Cr(VI) removal and its optimization - Arif, Z.; Sethy, N.K.; Mishra, P.K.; Verma, B. (Springer, 2020)
Mathematical modeling of a phase inversion membrane was studied to predict the morphology. The effect of different concentrations of TiO2 nanoparticles on the thermodynamic and kinetic properties of polyvinylidene fluoride (PVDF) membrane casting solutions was investigated. The addition of green synthesized TiO2 increases the viscosity, and a sufficient amount results in the formation of two phases. Thermodynamics enhances the demixing rate, whereas kinetics delays the demixing rate; this trade-off between thermodynamic and kinetic parameter will affect the membrane morphology. A quadratic phase diagram for PVDF/ TiO2/solvent/Water system was drawn experimentally at different concentrations of TiO2 using a new method. Synthesized membranes were characterized by the contact angle, porosity, and permeability. Surface morphologies at different compositions were also examined using High Resolution scanning electron microscope (HRSEM). At TiO2 concentration of 2 wt% in the polymer casting solution, thermodynamics parameter dominates kinetics parameter; thus, maximum porosity with enhanced permeability was achieved experimentally. The importance of thermo-kinetic parameters was further assessed using response surface optimization. The study suggested an optimum value of 2.165% of weight% TiO2 at 5.125 pH giving excellent agreement to the experimental data. © 2020, The Polymer Society, Taipei.
Keywords: Nanoparticle; Thermodynamic; Separation technique; Phase diagram